Variação Genética e ganho esperado na seleção de progênies de Pinus caribaea var. caribaea em Selvíria, MS - Silva, Janete Motta Da; Aguiar, Ananda Virgínia; Mori, Edson Seizo; Moraes, Mario Luiz Teixeira De (My University, 2011)
The present research has proposed to estimate the genetic variation of growth traits and to estimate the expected gain by multi-effect index (MEI), in order to transform a Pinus caribaea var. caribaea progeny trial into a seedling seed orchard. The progeny trial was set up in 1989, in Selvíria, MS, Brazil, using a 10 × 10 triple lattice design, with 99 progenies and a commercial control, with linear plots of ten plants, by the 3 × 3 m spacing between plants and rows. Total plant height, diameter at breast height (Dbh), wood volume, stem form, wood density at breast height, and survival were the evaluated quantitative traits. The trial was measured through 14, 15, and 16 years old. The 50% intensity of thinning at 14.3 years old was done. No significant was the genetic variation of different traits. Heritability estimates have presented low magnitude with low variation by the different ages. The application of MEI to DBH, at two years after thinning, resulted in higher gains than the selection of within and among progenies. The best selection strategy to obtain higher gains and to keep genetic diversity is to select until five plants per progenies.
Genetic variation and expected gain in selection of Pinus caribaea Morelet var. caribaea progenies in Selviria, MS
Keywords: Genetic divergence; Genetic parameters; Multi-effects index (MEI); Tropical pines